Review: Daphne M. Keats (2001). Interviewing: A Practical Guide for Students and Professionals - Froede, Emmeline (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2002)
KEATS' book "Interviewing: A practical guide for students and professionals" introduces interviewing and covers aspects such as why and what type of interviews can be used, before providing the reader with a step-by-step guide of what the important features are when interviewing and the difficulties that can be encountered. KEATS' book was considered to be extremely valuable and any criticisms made, were mere suggestions for future improvement. As KEATS said herself "It is not possible in a book of this scope to cover all kinds of interviews and all levels of interviewing skill", however this book has been thought out very carefully and is an excellent guide for any reader who is interested in interviewing. URN: urn:nbn:de:0114-fqs020183